2017
DOI: 10.3389/fneur.2017.00346
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Dynamic Causal Modeling of Resting-State fMRI Reveals Longitudinal Changes in Effective Connectivity in the Motor System after Thalamotomy for Essential Tremor

Abstract: Thalamotomy at the ventralis intermedius nucleus for essential tremor is known to cause changes in motor circuitry, but how a focal lesion leads to progressive changes in connectivity is not clear. To understand the mechanisms by which thalamotomy exerts enduring effects on motor circuitry, a quantitative analysis of directed or effective connectivity among motor-related areas is required. We characterized changes in effective connectivity of the motor system following thalamotomy using (spectral) dynamic caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 49 publications
(59 reference statements)
1
45
0
Order By: Relevance
“…Recently the rise of MRI-guided high-intensity focused ultrasound (MRgFUS) thermal ablation technique to produce a thalamotomy allowed the chance to use fMRI to study the changes in the brain network caused by a focal lesion. Two rs-fMRI studies performed in drug-resistant ET patients treated with MRgFUS, confirmed connectivity changes in the motor tremor network and not only in the target region 49,50 .…”
Section: Discussionmentioning
confidence: 68%
“…Recently the rise of MRI-guided high-intensity focused ultrasound (MRgFUS) thermal ablation technique to produce a thalamotomy allowed the chance to use fMRI to study the changes in the brain network caused by a focal lesion. Two rs-fMRI studies performed in drug-resistant ET patients treated with MRgFUS, confirmed connectivity changes in the motor tremor network and not only in the target region 49,50 .…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, microstructural changes were measured 3 months after tcMRgFUS thalamotomy. Although it has been proposed that functional changes stabilize between 1 week and 3 months after tcMRgFUS thalamotomy (Park et al, ), how these changes behave at longer follow‐ups has not yet been explored. Characterization of microstructural changes after longer periods is required to better describe long‐lasting effects and their correlation to clinical benefit, and to see if the resolution of the side effects is related to the shrinkage of the lesion, or to other distant effects, such as any contralateral compensatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The columns of the A matrix denote the region of neuronal activity origin and the rows denote the region being influenced. The estimated self-connection values, diagonal elements of the A matrix, in the spDCM output have units of Hz after exponentiation and multiplication by À0.5 (Park et al, 2017). Positive estimated self-connections indicate greater self-inhibition, while negative estimated self-connections represent less self-inhibition with respect to the prior (Park et al, 2017).…”
Section: General Linear Model and Region Of Interest Extractionmentioning
confidence: 99%
“…The estimated self-connection values, diagonal elements of the A matrix, in the spDCM output have units of Hz after exponentiation and multiplication by À0.5 (Park et al, 2017). Positive estimated self-connections indicate greater self-inhibition, while negative estimated self-connections represent less self-inhibition with respect to the prior (Park et al, 2017). Extrinsic connections, offdiagonal elements of the A matrix, have units of Hz and are excitatory when positive and inhibitory when negative.…”
Section: General Linear Model and Region Of Interest Extractionmentioning
confidence: 99%